Adenylyl cyclase isoforms 5 and 6 in the cardiovascular system: complex regulation and divergent roles - Maghsoudi, Saeid; Shuaib, Rabia; Van Bastelaere, Ben; Dakshinamurti, Shyamala (Frontiers in Pharmacology, 2024)
Adenylyl cyclases (ACs) are crucial effector enzymes that transduce divergent signals from upstream receptor pathways, and are responsible for catalyzing the conversion of ATP to cAMP.The ten AC isoforms are categorized into main four groups; the class III or calcium-inhibited family of ACs comprises AC5 and AC6. These enzymes are very closely related in structure and have a paucity of selecve acvators or inhibitors, making them difficult to disnguish experimentally.AC5 and AC6 are highly expressed in the heart and vasculature, as well as spinal cord and brain;AC6 is also abundant in the lungs, kidney, and liver. However, while AC5 and AC6 have similar expression paterns with some redundant funcons, they have disnct physiological roles due to differing regulaon and cAMP signaling compartmentaon. AC5 is crical in cardiac and vascular funcon; AC6 is a key effector of vasodilatory pathways in vascular myocytes, and is enriched in fetal/neonatal ssues. Expression of both AC6 and AC5 decreases in heart failure; but AC5 disrupon is cardio-protecve, while overexpression of AC6 rescues heart funcon in cardiac injury. This is a comprehensive review of the complex regulaon of AC5 and AC6 in the cardiovascular system, highlighng overexpression and knockout studies as well as transgenic models illuminang each enzyme, and focusing on post-translaonal modificaons that regulate their cellular localizaon and biological funcons. We also describe pharmacological challenges in the design of isoform-selecve acvators or inhibitors for AC5 and 6, which may be relevant to developing new therapeuc approaches for several cardiovascular diseases.